Noncommutative Multisoliton Solutions of a Supersymmetric Chiral Model - Xiujuan Zhu (Abstract and Applied Analysis)
Multisoliton configurations of a superextended and Moyal-type noncommutative deformed modified 2+1 chiral model have been constructed with the dressing method by Lechtenfeld and Popov several years ago. These configurations have no-scattering property. A two-soliton configuration with nontrivial scattering was constructed soon after that. More multisoliton solutions with general pole data of the superextended and noncommutative Ward model will be constructed in this paper. The method is the supersymmetric and noncommutative extension of Dai and Terng’s in constructing soliton solutions of the Ward model.